If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 16t + 31t + 6 Reorder the terms: 2 = 6 + 16t + 31t Combine like terms: 16t + 31t = 47t 2 = 6 + 47t Solving 2 = 6 + 47t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-47t' to each side of the equation. 2 + -47t = 6 + 47t + -47t Combine like terms: 47t + -47t = 0 2 + -47t = 6 + 0 2 + -47t = 6 Add '-2' to each side of the equation. 2 + -2 + -47t = 6 + -2 Combine like terms: 2 + -2 = 0 0 + -47t = 6 + -2 -47t = 6 + -2 Combine like terms: 6 + -2 = 4 -47t = 4 Divide each side by '-47'. t = -0.08510638298 Simplifying t = -0.08510638298
| 10y+7x=202 | | H=16t+31t+4 | | 0=16t+31t+4 | | H=16t+31t+6 | | 0=16t+31t+6 | | 7x+10y=202 | | 54y^2-20x^2=0 | | 55-4x=2 | | ln(6)+ln(x-6)=ln(x) | | 6=16t^2+31+4 | | 4=16t^2+31+6 | | H=16t^2+31+6 | | log3-3=1/27 | | 3-3=1/27 | | 5x+7=6x+2(2) | | 1.2=6(4-0.4g)-4.8 | | 2x+1=-(x-13) | | 75/925 | | -3.8x-5=-2.9x+4 | | G(-1)=-2y+2 | | 1/4d-1=7 | | 8+8=-16 | | G(-2)=-3x+8 | | 7/9y-4 | | 3=4(x-7)+2(10-x) | | 4x^3-48x^2+144x+9=0 | | (2/5)(10/2)= | | 9x^3-27x/18x^2 | | 5c-1=5c+6c | | 3.8/x^2=0.7 | | -1=-4t+2r | | -x^2+8.5x+4=0 |